Unmet needs in patients with acute myeloid leukemia ineligible for intensive approaches: perspectives from a European expert panel - Ferrara, Felicetto; Geissler, Klaus; Mehta, Priyanka; Montesinos, Pau; Venditti, Adriano (Frontiers in Oncology, 2025)
Acute myeloid leukemia (AML) is primarily a disease of the elderly, with increasing age associated with worse outcomes. Treatment options include intensive chemotherapy, hypomethylating agents with/without venetoclax, and best supportive care. Although the treatment landscape for AML has progressed in recent years, survival in older, frail patients ineligible for intensive chemotherapy remains poor. To address this, a panel of European experts convened to discuss the key factors influencing AML prognosis in older patients and/or those deemed unfit for intensive therapy. The panel shared perspectives on AML outcomes, patient fitness, treatment choices, and unmet needs. Experts agreed that although age is an important factor in guiding therapeutic decision making, other factors should also be considered such as comorbidities and the impact of disease biology (e.g., cytogenetic/molecular aberrations). Experts also agreed that more robust assessments of patient fitness are required, such as the utilization of geriatric assessment tools. As choice of therapy and its associated toxicities can impact patient’s quality of life (QoL), the logistical, psychosocial, and financial challenges experienced by the patient and their support network needs to be considered when determining treatment. Finally, experts agreed that outcomes in older, unfit patients with AML remain suboptimal in part due to the impact of treatment-related toxicities and QoL burden. There is therefore an urgent need for alternative treatments which minimize toxicity and reduce QoL burden.